Adventures of Sherlock Holmes. Vol. 2. (Solana Beach, CA Television Classics, 1954)
Arguably the greatest investigator of all time, Sherlock Holmes uses his sharp eye and quick wit to solve baffling crimes. His knowledge of a wide array of subjects makes him a nearly clairvoyant investigator, such that even his assistant Watson is surprised by his astute observations. Follow Holmes as he uses his deductive reasoning to unravel three enigmatic crimes.
Case of the Eiffel Tower -- Case of the French interpreter -- Case of Harry Crocker.
Based on the stories by Sir Arthur Conan Doyle.
"3 full-length episodes."
DVD, digitally remastered/sound enhanced.
113503
Keywords: Holmes, Sherlock; Watson, John H; Private investigators -- Drama; Detective and mystery television programs; England; Great Britain; Drama